Pengaruh Literasi Keuangan Syariah dan Islamic Branding Terhadap Keputusan Mahasiswa dalam Menggunakan Produk Perbankan Syariah: Studi Kasus pada Mahasiwa Program Studi Perbankan Syariah Umsu - Dini Erika; Siti Mujiatun (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to determine the influence of Sharia Financial Literacy and Islamic Branding on Students' Decisions to Use Sharia Banking Products (Case Study of Students of the UMSU Sharia Banking Study Program) both partially and simultaneously. This research approach is associative. The population is the entire UMSU Sharia Banking Student Study Program and the sample is 100 UMSU Sharia Banking Student Study Programs. Data collection techniques in this research used interview techniques, documentation studies, observations and questionnaires. The data analysis technique in this research uses Multiple Linear Regression Analysis Test, Hypothesis Test (t Test and F Test), and Coefficient of Determination. Data processing in this research used the SPSS (Statistical Package for the Social Sciences) software program version 29.00. Partially, the variable sharia financial literacy has a significant effect on students' decisions in using sharia banking products. Partially, the Islamic branding variable has a significant effect on students' decisions in using sharia banking products. Simultaneously, the variables Sharia Financial Literacy and Islamic Branding have a significant effect on students' decisions in using Sharia banking products.